Validation of a two-step simplified compatible homogenisation approach extended to out-plane loaded masonries. (3rd June 2019) - Bertolesi, Elisa; Silva, Luis Carlos; Milani, Gabriele
A two-step homogenisation model, formulated by the authors for the in-plane case, is herein extended for the nonlinear out-of-plane analysis of masonry structures. A rectangular running bond elementary cell is discretised by 24 elastic CST elements and inelastic zero-thickness interfaces. The mechanical meso-scale problem is briefly recalled, whereas the out-of-plane homogenised behaviour is evaluated by means of a simple on-thickness integration of the in-plane homogenised curves. At a macro-scale, the rigid body and spring model is slightly modified to allow both flexural and torsional failure mechanisms. The validation of the numerical approach is achieved comparing with some full-scale masonry panels tested in two-way bending up to failure. A series of nonlinear structural analyses are conducted considering different parameters, which have been varied during the experimental campaign. The numerical results are promising and demonstrate the capability to deal with different failure mechanisms as result of a combination of various experimental aspects.